Dead spy running - Stock, Jon (Blue Door London, 2010)
Daniel Marchant, a suspended MI6 officer, is running the London Marathon. He is also running out of time. A competitor is strapped with explosives. If he drops his pace, everyone around him will be killed, including the US ambassador to London. Marchant tries to thwart the attack, but is he secretly working for the terrorists? There are those in America who already suspect Marchant of treachery, just as they suspected his late father, the former head of MI6, who was removed from his job by the CIA. Marchant is treated like an enemy combatant - rendition, water-boarding - but he has friends ..